Respiratory rate detection by a time-based measurement system - Sifuentes, E.; Cota-Ruiz, J.; Gonzalez-Landaeta, R. (Revista Mexicana de Ingenieria Biomedica, 2016)
This paper proposes a system that converts a time-modulated signal from a resistive sensor into a digital signal with the goal to estimate the respiratory rate of a subject. To detect breathing, a known method based on a nasal thermistor, which detects temperature changes near the nostrils, is used. In this work, the thermistor mounted in a Wheatstone bridge, forms a RC circuit which is connected directly to a microcontroller, without using any analog circuit or analog-digital converter. Thus, whenever the subject breathes, it causes a fractional change in resistance x (Δ R/R0) on the thermistor, and this produces a time-modulated signal that is directly digitized with the microcontroller. Measurements were made on 23 volunteers, obtaining changes of x > 0.01. The temperature resolution was 0.2 °C, and the time response was 0.8 s, mainly limited by the thermistor properties; these features were enough to obtain a well-defined waveform of the breathing, from which was easy to estimate the respiratory rate by a compact, low cost and low power consumption system. Unlike interface circuits based on the voltage or current amplitude, with this kind of interface, the self-heating of the sensor is avoided since the thermistor does not require any voltage or bias current.